Factors influencing farmers' dis-adoption and retention decisions for biofortified crops: the case of orange-fleshed sweetpotato in Mozambique - Jogo, W.; Bocher, T.; Grant, F. (Informa UK Limited, 2021)
Despite their proven effectiveness in addressing micronutrient deficiencies, adoption of biofortified crops among smallholder farmers remains low. Using a cross-sectional survey dataset of 1538 households randomly selected from 15 districts in Nampula and Zambezia provinces of Mozambique, this study examined the factors influencing farmers' dis-adoption and retention decisions for biofortified OFSP varieties. Data on household socio-demographic characteristics; knowledge, attitudes, perceptions and practices on OFSP production and nutrition were fitted to a Heckman bivariate probit model with sample selection to empirically assess the determinants of sequential adoption and dis-adoption decisions. The results showed that adoption and dis-adoption of OFSP is significantly influenced by a combination of farmers' socio-economic characteristics (age, gender, nutrition knowledge, education, access to planting material), consumption (taste, dry matter content) and agronomic (yield, early maturity, drought tolerance) traits. However, the agronomic traits and access to planting material are particularly key for the retention of OFSP varieties. These results suggest the need for breeding efforts to improve the agronomic traits of biofortified OFSP to match or better local non-biofortified varieties and establish seed delivery systems for sustainable adoption of biofortified OFSP.